MinimaxX player load as an index of the center of mass displacement? A validation study - Hollville, E.; Couturier, A.; Guilhem, G.; Rabita, G. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this study was to assess the concurrent validity of the player load computed by the MinimaxX accelerometers by comparing it to the player load computed by a gold standard method based on in series force platforms. Fourteen participants were instrumented with two accelerometers (MinimaxX S4, Catapult, Australia) during specific team sport displacements performed on the force plates. Pearson correlation coefficients were ranged from 0.74 to 0.93 while the coefficients of variation varied from 6.9 to 16.4%. The standard error of the estimate was small (<0.6) or moderate (0.6-1.2). The validity of the accelerometers is good or very good for the different tested exercises. These results suggest the player load parameter computed with MinimaxX accelerometers seems able to characterize the physical demands in team sports